EFFORTS OF NAFTA FOR SETTLEMENT OF LINDANE PRODUCT DISPUTES CHEMTURA COMPANY WITH TRADE DISPUTES GOVERNMENT OF CANADA BASED ON UNCINTRAL - Fitri, Devy Lia; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses NAFTA's efforts to resolve the Lindane trade dispute between the Chemtura company and the Canadian government. The problem is that Lindane's products are prohibited from being manufactured and marketed which Canada violates the agreement.This study uses the perspective of Liberalism where this policy upholds world peace. The method used is descriptive with a qualitative approach which emphasizes the resolution of problems between two parties. The author uses the level of analysis of the nation state. At the level of analysis of the state, there is an assumption that all decision-makers, wherever they are, will essentially behave the same way in dealing with all the same situations and conditions.The results of the study show that the judicial results decided that Canada did not violate the article referred to by Chemtura and Chemtura had to pay a fine of $2,889,233.80 Canadian.Keywords: Liberalism, Role of International Organizations, Trade Disputes, Role of NAFTA